Improving Financial Planning Graduate Employability Through Enterprise Education - John Teale (Australasian Accounting, Business and Finance Journal, 2013)
Financial planning requires students to display tacit learning. However, the traditional teaching approach concentrates on theory development independent of any applied connection with the profession. This paper uses an adaptation of the Goetz et al. (2005) model to demonstrate how curricula can provide a smoother progression into the financial planning profession. Further, a number of teaching strategies are described to provide a closer connection with the profession.
Keywords: financial planning education; curriculum reform; financial planning; higher education